Intermediality and storytelling - Grishakova, Marina; Ryan, Marie-Laure, 1946- (Narratologia, 2010)
Extending narratological analysis to media as varied as graphic novels, photography, television, musicals, computer games and advertising, the essays gathered in this volume address some of the most fundamental questions raised by the medial turn in narratology: how can narrative meaning be created in media other than language; how do different types of signs collaborate with each other in so-called 'multimodal works'; and what new forms of narrativity are made possible by the emergence of digital media.